WEBVTT
00:00:00.830 --> 00:00:06.470
Simplify π plus two factorial divided by π factorial.
00:00:07.730 --> 00:00:17.060
We recall that π factorial is equal to π multiplied by π minus one multiplied by π minus two all the way down to one.
00:00:17.930 --> 00:00:24.440
We need to multiply all of the integers or whole numbers from our number down to one.
00:00:25.670 --> 00:00:39.290
In order to calculate π plus two factorial, we would need to multiply π plus two by π plus one by π by π minus one by π minus two all the way down to one.
00:00:40.200 --> 00:00:44.820
We notice that from π onwards is equal to π factorial.
00:00:46.160 --> 00:00:55.320
π plus two factorial is therefore equal to π plus two multiplied by π plus one multiplied by π factorial.
00:00:56.530 --> 00:01:07.790
If we substitute this into our question, we have π plus two multiplied by π plus one multiplied by π factorial all divided by π factorial.
00:01:08.840 --> 00:01:11.850
Any number divided by itself is equal to one.
00:01:12.120 --> 00:01:16.270
Therefore, π factorial divided by π factorial is one.
00:01:17.120 --> 00:01:22.420
We are therefore left with π plus two multiplied by π plus one.
00:01:23.210 --> 00:01:32.000
Whilst we could distribute the parentheses or expand the brackets here, we donβt need to, as the expression is already in its simplest form.
00:01:32.710 --> 00:01:42.500
The simplified version of π plus two factorial divided by π factorial is π plus two multiplied by π plus one.